A cohort analysis of household saving in Norway - Elin Halvorsen (University of Oslo, Department of Economics, 2002)
In this paper I study the role of generational differences in saving. My main evidence is an empirical analysis based on Norwegian data that show a tendency for older birth cohorts to have higher saving rates, but that the differences are small and statistically insignificant. Consequently, the high aggregate saving rate and the very high saving among the elderly cannot be primarily attributed to cohorts effect. To ensure that the findings are robust, a variety of econometric specifications and techniques are employed.
Keywords: D91; E21; 330; Lifecycle models and saving; age; period and cohort effects; robust estimation; Sparen; Generationenbeziehungen; Norwegen